2009
DOI: 10.1080/01443610903039153
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of team communication in an obstetric emergency scenario

Abstract: We studied a random sample of four teams of doctors and midwives who participated in a videotaped simulated obstetric emergency, postpartum haemorrhage, before and after 'on-site' clinical training. We aimed to assess the validity of mixed techniques for the analysis of team communication and whether clinical and non-clinical team training improve communication. Two of the four teams received extra training in specific teamwork behaviours (TW+), the other half received only clinical training (TW-). We used con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…Fifteen articles met our inclusion criteria, which represented 12 independent studies (Boet et al, 2013;Crofts et al, 2007Crofts et al, , 2008Daniels et al, 2010;Ellis et al, 2008;Frengley et al, 2011;Jankouskas, Haidet, Hupcey, Kolanowski, & Murray, 2011;LeFlore & Anderson, 2009;Miller, Crandall, Washington, & McLaughlin, 2012;Phipps et al, 2012;Riley et al, 2011;Shapiro et al, 2004;Siassakos, Draycott, Montague, & Harris, 2009;Thomas et al, 2007Thomas et al, , 2010. Four of the articles included in the review were companion reports from the UK SaFE trial and, together were considered one independent study (Crofts et al, 2007Ellis et al, 2008;Siassakos et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen articles met our inclusion criteria, which represented 12 independent studies (Boet et al, 2013;Crofts et al, 2007Crofts et al, , 2008Daniels et al, 2010;Ellis et al, 2008;Frengley et al, 2011;Jankouskas, Haidet, Hupcey, Kolanowski, & Murray, 2011;LeFlore & Anderson, 2009;Miller, Crandall, Washington, & McLaughlin, 2012;Phipps et al, 2012;Riley et al, 2011;Shapiro et al, 2004;Siassakos, Draycott, Montague, & Harris, 2009;Thomas et al, 2007Thomas et al, , 2010. Four of the articles included in the review were companion reports from the UK SaFE trial and, together were considered one independent study (Crofts et al, 2007Ellis et al, 2008;Siassakos et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies involved interprofessional teams (Crofts et al, 2007Daniels et al, 2010;Ellis et al, 2008;Frengley et al, 2011;Jankouskas et al, 2011;Shapiro et al, 2004;Siassakos et al, 2009), and five were both interprofessional and interdisciplinary (Boet et al, 2013;LeFlore & Anderson, 2009;Miller et al, 2012;Phipps et al, 2012;Riley et al, 2011), while two only involved interdisciplinary teams (Thomas et al, 2007(Thomas et al, , 2010. Physicians and nursing were the most common professions, represented in 12 and 9 studies, respectively.…”
Section: Team Profilesmentioning
confidence: 97%
See 2 more Smart Citations
“…15 However, a detailed analysis of this study demonstrated that additional teamwork training resulted in an improvement in directed and addressed messages, as opposed to those called out in the air, but this was not associated with improved clinical performance. 22 It has been shown recently that some teamwork characteristics are important for a healthcare team to work efficiently, 23,24 and in a manner that is evaluated positively by patient-actors. 25 Therefore, generic teamwork training may be important, but may need to become more context specific before it can translate into better outcomes.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%